A closer look at the Ebola outbreak in West Africa. (May 2015) - Borchert, Matthias; Saez, Almudena Mari; Kratz, Thomas
Matthias Borchert, MD MSc PhD, is a medical epidemiologist. After clinical work in Hamburg, he joined the German Volunteer Service as a District Medical Officer in rural Burkina Faso. Later, he joined the Heidelberg Department of Tropical Hygiene and Public Health, the Antwerp Institute of Tropical Medicine, the London School of Hygiene and Tropical Medicine and the Institute of Tropical Medicine and International Health, Charité – Universitätsmedizin Berlin. He has an MSc in epidemiology and a PhD on 'Epidemiology and Control of Marburg Haemorrhagic Fever Epidemics in Central Africa'. He teaches epidemiology, statistics, safe motherhood and control of viral hemorrhagic fevers. His research interests are safe motherhood and viral hemorrhagic fevers in sub-Saharan Africa. He has contributed five times to Ebola/Marburg outbreak response. Almudena Marí Sáez is a postdoctoral fellow at Institute of Tropical Medicine and International Health Charité - Universitätsmedizin Berlin. She is working on Lassa fever in Guinea and Sierra Leone: rodent control, and seasonality of human exposure to rodents – a project supported by a research grant from the German Research Foundation (DFG BO3790/1-1). She has been involved in Ebola response in Guinea and Liberia as anthropologist. Her previous ethnographic work focused on maternal health and local medicines in Benin and Sierra Leone. Thomas Kratz, MD, undertook medical studies in Marburg/Germany and Strasburg (France) in order to obtain his medical degree in 2003. He worked as an assistant doctor in Strasburg and several hospitals in Germany with obtaining the specialization of a GP in 2014. Since 2007, He worked as a medical doctor in missions with Médecins sans Frontières (MSF). He commenced postgraduate Studies in International Health in Berlin in 2010, as by the beginning of 2015 finalization of Master's Thesis upon Bundibugyo Ebolavirus disease. Since the end of 2014, he is working with a focus on special pathogens for the Robert Koch Institute in Berlin (Germany), a Federal institute within the portfolio of the Federal Ministry of Health.